2015
DOI: 10.1111/aor.12448
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of Pre‐pump Arterial Pressure to Avoid Inadequate Dialysis and Hemolysis: Importance of Prepump Arterial Pressure Monitoring in Hemodialysis Patients

Abstract: Prepump arterial pressure (PreAP) is monitored to avoid generating excessive negative pressure. The National Kidney Foundation K/DOQI clinical practice guidelines for vascular access recommend that PreAP should not fall below -250 mm Hg because excessive negative PreAP can lead to a decrease in the delivery of blood flow, inadequate dialysis, and hemolysis. Nonetheless, these recommendations are consistently disregarded in clinical practice and pressure sensors are often removed from the dialysis circuit. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…Such pressures can decrease the delivery of blood flow, result in inadequate dialysis and lead to haemolysis. Even pressure values below −150 mmHg have been shown to induce haemolysis …”
Section: Causesmentioning
confidence: 99%
“…Such pressures can decrease the delivery of blood flow, result in inadequate dialysis and lead to haemolysis. Even pressure values below −150 mmHg have been shown to induce haemolysis …”
Section: Causesmentioning
confidence: 99%
“…Over time the standard blood pump for dialysis circuits changed from a small three headed peristaltic rotatory positive displacement pump to the current two headed rotary pump. Clinical studies using blood flows < 350 ml/min were unable to demonstrate red cell fragmentation, but laboratory studies reported increased haemolysis with blood flows increasing above 300 ml/min with increasing pre-pump pressures of -150 mmHg [4,5]. This mechanical trauma to cells is reduced by using lower pump speeds, but also by redesigning the blood pump.…”
Section: Improving the Design Of The Extracorporeal Circuitmentioning
confidence: 99%
“…Eriko Shibata et al of the University of Tokushima, Tokushima, Japan evaluated the importance of prepump arterial pressure (PreAP) and delivered flow or PreAP and hemolysis in the prediction of inadequate dialysis and hemolysis. By using different diameter needles, human blood samples from healthy volunteers were circulated in a closed dialysis circuit.…”
Section: Renal Supportmentioning
confidence: 99%